Historical overview of agricultural production in Ukraine (2018-2022): Background insight into the impact of the Russo-Ukrainian war on local, regional and global food security: Global food security: Consequence of the Russo-Ukrainian war - Teixeira da Silva, Jaime A.; Koblianska, Inna; Kucher, Anatolii (Journal of Agricultural Sciences (Belgrade), 2023)
The ongoing Russo-Ukrainian war, following the invasion of Ukraine by the Russian Federation on February 24, 2022, is affecting Ukrainian agriculture, including the inability of Ukraine to export agricultural products, such as grains and cereals, to regional (European) and international markets by sea, although that was partly alleviated by the creation of a ‘grain corridor’. As a result, food security in Ukraine, the region (EU) and globally, is at risk, especially nations that rely heavily on agricultural imports from Ukraine. This paper provides a unique appreciation of these issues by providing a background context of Ukrainian agricultural production using available statistics from 2018-2022, based on the English literature and on official Ukrainian government statistics.